2019
DOI: 10.1038/s41598-019-40374-3
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the relationship between taste perception and oral microbiota composition

Abstract: Fairly poor data are available on the relationship between taste perception, food preferences and oral microbiota. In the present study, we investigated the hypothesis that subjects with higher responsiveness to 6-n-propylthiuracil (PROP) might be characterized by a different taste sensitivity and tongue microbiota composition. Indeed, the bacterial metabolism may modulate/enhance the concentration of tastants near the taste receptors, modifying taste perception through a sensorial adaptation mechanism or by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 62 publications
(55 reference statements)
7
56
1
1
Order By: Relevance
“…There was an unseen benefit to this lesson. Our detailed examination of every data-collection method employed in the taste field led us to develop the Denver Papillae Protocol (DPP) to count FP consistently ; DPP is now used in many academic taste labs (Cattaneo et al 2019;Reynolds et al 2017;Spinelli et al 2017), and researchers attempting to automate FP counts have used DPP to check the accuracy of their proposed methods (Eldeghaidy et al 2018;Piochi et al 2017). The taste-research community ultimately benefited from our experience, even if our original data didn't advance the field's understanding of the genetics of taste.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…There was an unseen benefit to this lesson. Our detailed examination of every data-collection method employed in the taste field led us to develop the Denver Papillae Protocol (DPP) to count FP consistently ; DPP is now used in many academic taste labs (Cattaneo et al 2019;Reynolds et al 2017;Spinelli et al 2017), and researchers attempting to automate FP counts have used DPP to check the accuracy of their proposed methods (Eldeghaidy et al 2018;Piochi et al 2017). The taste-research community ultimately benefited from our experience, even if our original data didn't advance the field's understanding of the genetics of taste.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The bacterial community structure of the fecal microbiota was analyzed as described elsewhere [23,24], with DNA extracted from feces as described in Section 2.2. In brief, extracted DNA was analyzed through 16S rRNA gene profiling.…”
Section: Analysis Of the Bacterial Taxonomic Composition Of Fecal Sammentioning
confidence: 99%
“…Taste modulation could therefore rely on basal saliva components. Physical‐chemical interactions of salivary proteins with bitter tastants, release of simple sugars through amylase activity or buffering of acids through carbonic anhydrase activity may occur and some components of basal saliva such as ions, proteins or even sugars may act as tastants . An accumulation of bacterial plaque may moreover cover the tongue and could also refer to “tongue coating” sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Tongue coating reduction enhanced taste ability, suggesting that tongue coating limits tastants’ access to taste pores and thus prevents their binding to taste receptors. Cattaneo et al, recently demonstrated that the number of Gram‐positive Actinomyces , Oribacterium , Solobacterium and Catonella , and Gram‐negative Campylobacter populations on the tongue dorsum was higher in PROP‐supertasters compared with PROP‐non‐tasters, suggesting that lingual microbiota may vary according to taste phenotype or ability. Correlations have also been observed between bitter taste sensitivity and Bacteroidetes of the lingual biofilm .…”
Section: Discussionmentioning
confidence: 99%